Factors Influencing the Successful Implementation of Talent Management in the Indonesian Ministry of Finance - Rifai, Ahmad; Maarif, M. Syamsul; Sukmawati, Anggraini (UI Scholars Hub, 2023)
Talent management has been widely discussed since the introduction of The War for Talent. This study aims to analyze factors that influence the successful implementation of talent management in the Ministry of Finance and analyze employee perceptions and priorities for talent management development. The population in this study included 80,996 employees of the Ministry of Finance, with a total sample of 408 people. The research employed a descriptive approach and Importance Performance Analysis (IPA). The results indicate that organizations need to motivate and facilitate employees to adapt to organizational developments, provide equal opportunities for growth for all employees, develop the competence of the HR Department to handle talent management challenges and provide a comprehensive repository of talent management information. Meanwhile, the performance indicator that needs to be improved is providing equal opportunities for development for all employees.